Contribution to the study of higher education of the Argentine Republic. A journey through the History of the National University of Córdoba (2019)
Part of this text was read in the panel session organized by Dr. Diana Soto Arango on the occasion of the VI International Congress on History and Prospective Studies of the Universities of Europe and America CIHPUEA), held in the city of Tunja from 10 to 12 October, 2016. The aim of the congress was to contribute to revisit the history of Argentine universities, with special emphasis on the history of the National University of Córdoba. Taking into account the title of this work and considering the broad period of study, from the founding of the university to its current situation, we limit ourselves to the study of the construction of its legal framework and its agenda during the last decades of the twentieth century. Primary sources were used, some of them located in the archives of the University of Córdoba, press collections, specific bibliography, and my own previous research work. Methodologically, the work starts from a critical review of what has been done so far and aims to characterize the different historical moments analyzed with their corresponding particularities. The choice of texts was made following the simple criterion of trying to illuminate the topics we have addressed previously so that the material serves as a reference in different lines of thought.